2008
DOI: 10.1523/jneurosci.1170-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Synaptic Adhesion with Dendritic Spine Remodeling by AF-6 and Kalirin-7

Abstract: Remodeling of central excitatory synapses is crucial for synapse maturation and plasticity, and contributes to neurodevelopmental and psychiatric disorders. Remodeling of dendritic spines and the associated synapses has been postulated to require the coordination of adhesion with spine morphology and stability; however, the molecular mechanisms that functionally link adhesion molecules with regulators of dendritic spine morphology are mostly unknown. Here, we report that spine size and N-cadherin content are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 41 publications
8
94
0
Order By: Relevance
“…PAK is a molecular target of activated Rac, and is an important regulator of the actin cytoskeletal rearrangements that underlie spine remodeling. Activation of a Rac/PAK pathway induces larger spines (20)(21)(22); thus, we hypothesized that activation of 5-HT 2A receptors influences PAK signaling. We incubated cultured cortical neurons with DOI and examined phosphorylation of PAK on residue T423; phosphorylation at this site is indicative of activation by GTP-bound Rac1 or Cdc42 (31).…”
Section: -Ht2amentioning
confidence: 99%
See 1 more Smart Citation
“…PAK is a molecular target of activated Rac, and is an important regulator of the actin cytoskeletal rearrangements that underlie spine remodeling. Activation of a Rac/PAK pathway induces larger spines (20)(21)(22); thus, we hypothesized that activation of 5-HT 2A receptors influences PAK signaling. We incubated cultured cortical neurons with DOI and examined phosphorylation of PAK on residue T423; phosphorylation at this site is indicative of activation by GTP-bound Rac1 or Cdc42 (31).…”
Section: -Ht2amentioning
confidence: 99%
“…Kalirin-7 is enriched in the postsynaptic density of excitatory synapses in the mammalian forebrain, and its activation enhances Rac activation, p21-activated kinase (PAK) phosphorylation, dendritic spine maintenance and morphogenesis, and AMPA receptor trafficking (19)(20)(21). Kalirin-7 interacts with several synaptic protein complexes in neurons, including complexes associated with EphB receptors (21), NMDA receptors (20), and N-cadherin (22). The PDZ-binding motif located on the C terminus of kalirin-7 mediates its interaction with PSD-95 (20), and may allow it to interact with other PDZdomain-containing proteins (19).…”
mentioning
confidence: 99%
“…Since N-cadherin signaling leads to modulation of spine morphology and synapse stability (Abe et al, 2004;Xie et al, 2008;Mendez et al, 2010), we asked whether the increased synaptic accumulation of N-cadherin FL, as obtained by TAT-Pro treatment, could be paralleled by modifications of spine morphology.…”
Section: Adam10 Localization and Activity At Synapse Influence Spine mentioning
confidence: 99%
“…ADAM10 localization and activity influence subunit composition of synaptic AMPA receptors N-Cadherin regulates the number of AMPA receptors at synapses (Liao et al, 1999;Togashi et al, 2002;Kasai et al, 2003) and can interact with specific subunits of AMPA receptors (Dunah et al, 2005;Nuriya and Huganir, 2006;Saglietti et al, 2007). More recently, it has been shown that N-cadherin inactivation results in fewer GluR1 synaptic clusters (Xie et al, 2008).…”
Section: Adam10 Localization and Activity At Synapse Influence Spine mentioning
confidence: 99%
See 1 more Smart Citation